Foreign experience of non-governmental detective work to avoid and prevent crime. (Journal of actual problems of jurisprudence, 2016)
This research article discusses the international experience of non-governmental detective work in warning and prevention of crime. The author had made an analysis of the experience of foreign countries in the prevention and crime prevention, as well as implementation issues disclosed detective work in the Republic of Kazakhstan. Recommendations for further improvement of the non-state detective work in foreign countries.
Keywords: the fight against crime; detective work; crime prevention; the international experience